Glomerulonephritis among Saudi Children: Current Status Evaluation - Alenazi, Shehab Ahmed (Journal of Liaquat University of Medical & Health Sciences, 2024)
Glomerulonephritis (GN) is a common renal problem affecting children and is manifested by hematuria, proteinuria, fluid retention, and hypertension with altered glomerular filtration. This condition may be primary or developed secondary to other systemic diseases, immune disorders, infections, or drugs induced with different histopathological patterns and a wide range of clinical manifestations. The current study helps record and comprehend GN’s epidemiology in Saudi Arabia. Additional research is recommended that includes a more thorough examination of the prognostic factors, therapies, illness progression, and outcomes. While there are several advantages to having a GN registry that collects data in the future, resource constraints frequently prevent the establishment of comprehensive registries. Expanding research endeavors will play a significant role in fostering a healthy society and may provide insight into the underlying pathology of fascinating glomerulopathies.